CarVenience Enterprise / Marelfira Mahamud ... [et al.] - Mahamud, Marelfira; M Naser, Zulfikarnor; Jamil, Nur Diyana; Dzulkifli, Fatin Nadia; Ma'moon, Noraini (2019)
CarVenience Enterprise is a business that can be categorized as Small Medium Enterprise (SME) which provided rental of transportation and to specified is rental of car to the targeted customer. We are expert in managing transportation which is the most important elements to public that require to go from one destination to another destination. CarVenience Enterprise consists of five partnership business whose contribute same amount of capital and will hold different task and responsibilities based on education and previous work experience in order to manage our business. Through the long term observation, we had planned to setup this business because we can see wider prospect in this sector for the future. In addition, we discover that people are desire for owned car but fail to do that but still have intention to drive car by ourselves.